2014
DOI: 10.3109/09273948.2014.916309
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Choroidal Thickness in Children with Familial Mediterranean Fever

Abstract: The retinal and choroidal thicknesses of children with FMF do not differ from those of age- and sex-matched healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Further analysis of the results requested in a letter by Uzun et al 54 revealed no effect of either refractive error or the presence or absence of the M694V mutation. 55 These results were generally consistent with those reported by Erdurmuş et al 61 and were perhaps not unsurprising, given how uncommon retinal findings are in patients with FMF.…”
supporting
confidence: 88%
“…Further analysis of the results requested in a letter by Uzun et al 54 revealed no effect of either refractive error or the presence or absence of the M694V mutation. 55 These results were generally consistent with those reported by Erdurmuş et al 61 and were perhaps not unsurprising, given how uncommon retinal findings are in patients with FMF.…”
supporting
confidence: 88%
“…Correlations between the variables were investigated using the Pearson or Spearman correlation coefficient. The choroidal thickness data for healthy subjects in Erdurmus et al's [28] study (352.1 ± 60.0 µm) were used in order to calculate the required sample size to find a subfoveal choroidal thickness difference of 10% between the control group and FMF patients. For this purpose, an α error of 5% and a β error of 20% were used.…”
Section: Methodsmentioning
confidence: 99%
“…We congratulate Erdurmus et al 1 for their study entitled ''Retinal and Choroidal Thickness in Children with Familial Mediterranean Fever.'' The authors found that retinal and choroidal thickness did not differ significantly between familial Mediterrenean fever (FMF) patients and healthy controls.…”
mentioning
confidence: 99%